2019
DOI: 10.1016/j.bbrep.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular heavy chain-modification of hyaluronan during endotoxic shock

Abstract: During inflammation, the covalent linking of the ubiquitous extracellular polysaccharide hyaluronan (HA) with the heavy chains (HC) of the serum protein inter alpha inhibitor (IαI) is exclusively mediated by the enzyme tumor necrosis factor α (TNFα)-stimulated-gene-6 (TSG-6). While significant advances have been made regarding how HC-modified HA (HC-HA) is an important regulator of inflammation, it remains unclear why HC-HA plays a critical role in promoting survival in intraperitoneal lipopolysaccharide (LPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Furthermore, IαI has been shown to bind extracellular histones and neutralize histone-induced adverse effects in sepsis [49]. Finally, we recently described that IαI complexing with hyaluronan in septic animals leading to its rapid clearance and ameliorated sepsis mortality [50,51]. This suggests that IαI is able to reduce the inflammatory cascade in injured endothelia through many pathways, ultimately leading to reduced VCAM-1 and ICAM-1 upregulation and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IαI has been shown to bind extracellular histones and neutralize histone-induced adverse effects in sepsis [49]. Finally, we recently described that IαI complexing with hyaluronan in septic animals leading to its rapid clearance and ameliorated sepsis mortality [50,51]. This suggests that IαI is able to reduce the inflammatory cascade in injured endothelia through many pathways, ultimately leading to reduced VCAM-1 and ICAM-1 upregulation and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Initial SPR screening experiments with the 50-kDa and H120 fragments of fibronectin (see (51)), corresponding to the cell-ITIH1 structure reveals roles in inflammation & ovulation and heparin-binding regions, respectively, indicated that while both bound to rHC1 (in a metal ion-independent manner), the interaction with H120 was of considerably higher affinity than that with the 50-kDa fragment; the H120* fragment (missing the 12-13 type III repeats, but otherwise identical to H120) did not bind to rHC1. Therefore, we expressed fibronectin type III repeats 13-14 (denoted as cFN13- 14) in Escherichia coli, purifying this to homogeneity (see Figure S7 and Experimental Procedures), and showed that this bound rHC1 in an essentially identical fashion to H120; i.e. localizing the high affinity HC1-binding site on fibronectin to the 13-14 type III domains.…”
Section: Resultsmentioning
confidence: 99%
“…TSG-6 plays a catalytic role in transferring HCs from the CS chains of IαI and PαI onto HA to form HC•HA complexes (8,9); where this is essential for female fertility (10)(11)(12)(13). As well as being expressed by cumulus cells during ovulation, TSG-6 is also produced in the context of inflammation, where it mediates the formation of HC•HAs (14), e.g. when IαI/PαI leak into tissues from the blood circulation (reviewed in (9)).…”
Section: Immunity Protein Structure Proteoglycan Reproduction X-rmentioning
confidence: 99%
See 1 more Smart Citation
“…In select experiments, lipopolysaccharide (LPS) (20 μg) was dissolved in 50 μL of phosphate‐buffered saline and injected into the donor airway before connecting donor and recipient bronchi (Sigma). The concentrations and administration route were based on previous studies examining the impact of Pam 3 Cys 4 and LPS on pulmonary immune responses 12‐14 . For select experiments, 10 × 10 6 CD8 + T cells (Ly‐2 microbeads, Miltenyi Biotec, Bergisch Gladbach, Germany) 15 or 3 × 10 6 monocytes (Monocyte Isolation Kit, Miltenyi Biotec), 16 isolated from the spleen or bone marrow, respectively, of naïve B6 WT mice were injected intravenously into B6 TLR2KO recipients at the time of transplantation.…”
Section: Methodsmentioning
confidence: 99%